Raízes da Lusofilia de Gilberto Freyre - Chacon, Vamireh (Ciência & Trópico, 2011)
RESUMO Trata das relações afetivas e intelectuais de Gilberto Freyre com Portugal, mostrando como elas se inserem em sua obra ensaística e como remontam à influência do historiador Oliveira Lima sobre o autor de Casa-grande & senzala. Destaca, por isso, vários fragmentos da obra freyriana em que são valorizados o mar, o campo, a culinária, os azulejos e as regiões portuguesas. ABSTRACT Roots of Gilberto Freyre’s Lusophilia. v. 26, n. 1, p. 47-88, jan./jun. 1998. Studies the affective and intellectual Gilberto Freyre’s bonds with Portugal, showing how they are inserted in his essays and how they come from the historian Oliveira Lima´s influence on the author of The Masters and Slaves (Casa-grande & senzala). Stresses many parts of Freyre’s work in which he shows his special regard in relation to the sea, the country, the cookery, the wall tiles, and the Portuguese regions. RÉSUMÉ Racines de la Lusophilie de Gilberto Freyre. v. 26, n. 1, p. 47-88, jan./jun. 1998. Remontant à l’influence que l’historien Oliveira Lima a exercé sur l’auteur de Maîtres & Esclaves, l’article porte sur les relations affectives et intellectuelles entre Gilberto Freyre et le Portugal. A cet égard, il se penche sur plusieurs textes extraits de l’oeuvre freyrienne dans lesquels certains éléments comme la mer, la campagne, la gastronomie, les carreaux et les régions portugaises, jouent un rôle très important.